Characterization of the molecular mechanism underlying the dwarfism of dsh mutant watermelon plants. (December 2021) - Dong, Wei; Wu, Dewei; Wang, Caihui; Liu, Ying; Wu, Defeng
Highlights: The dsh is a GA-deﬁcient mutant and useful germplasm resource. Mutations in the promoter of ClaGA20ox2 mediate the dwarfism. Abstract: Developing dwarf watermelon is a major objective among breeders. The dsh dwarf watermelon germplasm developed in our laboratory is genetically stable. We previously produced preliminary evidence that Cla010726, which encodes a gibberellin 20-oxidase-like protein, is the primary gene controlling dwarfism in watermelon. However, the underlying genetic mechanism was unknown. In this study, we characterized the spontaneous recessive mutant dsh, which is a gibberellin (GA)-deﬁcient mutant. Many of the phenotypic traits of dsh plants are similar to those of known GA-deﬁcient mutants. The dsh plants were sensitive to exogenous bioactive GAs, which increased seedling height. Moreover, a quantitative analysis of endogenous GA3 proved that the bioactive GA3 content was substantially lower than normal in dsh . Additionally, the T5 ClaGA20ox RNAi plants generally exhibited dwarfism, with short stems and internodes as well as small leaves and fruit. An examination of the transgenic plants carrying the ClaGA20ox1 promoter-GUS and mutant ClaGA20ox2 promoter-GUS constructs confirmed that two promoter sites are involved in the regulation of ClaGA20ox expression. Hence, mutations in the promoter of the GA20ox gene, which encodes a key enzyme involved in gibberellin biosynthesis, lead to the dwarfism of watermelon plants. The dsh mutant is a potentially useful germplasm resource for developing new watermelon varieties exhibiting dwarfism.